The Transformation of Audiovisual Entertainment: From Traditional Television to Live Streaming - Mora de la Torre, Victoria; López Martín, Laura (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The media landscape is undergoing a profound transformation, driven by the emergence of digital content creators who harness platforms such as Twitch and YouTube to engage audiences traditionally loyal to conventional television. A notable example is ‘La Velada del año IV’, organised by Ibai Llanos, whose impact is examined through content analysis and social media data from Brand24. The findings highlight a shifting media paradigm characterised by participatory and decentralised dynamics, raising important questions about the future of traditional television in an increasingly interactive, creator-led digital ecosystem.